Adhesion of metallic glass and epoxy in composite-metal bonding. (1st February 2018) - Hamill, Lee; Nutt, Steven
Abstract: We report the effects of surface preparation on the adhesive strength between a bulk metallic glass (BMG) alloy and carbon fiber reinforced epoxy. The motivation of the study was to explore the potential for BMG alloys to be laminated with carbon fiber (CF) composites in fiber metal laminates (FMLs), structures in which galvanic coupling with the metallic component (aluminum) generally precludes the use of CF composites. Select surface treatment methods were performed on both BMG and aluminum samples, and the surfaces were subsequently compared via scanning electron microscopy (SEM) and measurements of water contact angle (WCA) and roughness. Results of characterization experiments indicated that the BMG alloy responded to surface treatments much like aluminum, and that these treatment methods when applied to BMGs promoted adhesion. Lap shear tests were also performed to evaluate the bond quality at composite-metal interfaces. The bond strength at the BMG-composite interface was as strong or stronger than aluminum-composite interfaces, with the exception of samples pre-treated by anodization.